Electrical and optical properties of chalcedony and striped chalcedony - Cetin, A.; Okutan, M.; Icelli, O.; Yalcin, Z.; San, S. E.; Kibar, R.; Pesen, E. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The electrical and optical properties of chalcedony (SiO2) and striped chalcedony are determined by the impedance and optical absorption spectroscopy techniques. The capacitance, impedance, dissipation factor and the complex dielectric constants are measured by the parallel plate technique in the voltage frequency range 100 to 10 MHz. The dissipation factor is measured as 1.2 and 0.7 for chalcedony and striped chalcedony respectively around 10 kHz. It is found that the striped chalcedony has a major complex broad band with two absorption bands that are centered at 225 and 275 nm. The chalcedony however, has a minor absorption band which is centered at 210 nm. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Chalcedony; Mineral; Permittivity; Dissipation factor; Absorbance; FILMS; Materials Science; Physics